2017
DOI: 10.1111/dar.12569
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural variation in the association between family's socioeconomic status and adolescent alcohol use

Abstract: Socioeconomic disparities in adolescent alcohol use vary across European countries. Broad country-level indicators can explain this variation only to a limited extent, but results point towards slightly greater socioeconomic disparities in drinking in countries of low national income and countries with a high income inequality. [Gomes de Matos E, Kraus L, Hannemann T-V, Soellner R, Piontek D. Cross-cultural variation in the association between family's socioeconomic status and adolescent alcohol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…This, too, is a research question in its own right, which is investigated in Beutel and colleagues [29], among others. Further, conclusions can be drawn with regard to the population group studied, since it can be assumed that countries differ in terms of the social determinants of health and well-being [3033].…”
Section: Discussionmentioning
confidence: 99%
“…This, too, is a research question in its own right, which is investigated in Beutel and colleagues [29], among others. Further, conclusions can be drawn with regard to the population group studied, since it can be assumed that countries differ in terms of the social determinants of health and well-being [3033].…”
Section: Discussionmentioning
confidence: 99%
“…The reported evidence from adolescent samples and from men in east Africa clearly indicates that affordability of alcohol plays a role in the occurrence of binge drinking. This points to the importance of price increases by means of taxation, which was repeatedly shown to be among the most effective alcohol‐related public health policy measures .…”
Section: Discussionmentioning
confidence: 96%
“…Investigating 32 European countries, Gomes de Matos et al . also found that drunkenness was more likely among adolescents from wealthier families but lower when parents were highly educated. Thus, it appears that the protection that higher education may offer is undermined by the higher income highly educated parents tend to have.…”
Section: Effects Of Immigration Acculturation‐related Stress Socio‐mentioning
confidence: 87%
See 1 more Smart Citation
“…Socioeconomic status (SES) is one of several factors that influence substance use among individuals across the lifespan (Jones et al, 2016). Numerous studies have investigated the association between different SES indicators and the use of alcohol and other substances during adolescence and young adulthood (Humensky, 2010; Patrick et al, 2012; Finch et al, 2013; Kendler et al, 2014; Latvala et al, 2014; Lui et al, 2015; Pedersen et al, 2015; Charitonidi et al, 2016; Non et al, 2016; Gomes de Matos et al, 2017; Jang et al, 2017; Pape et al, 2017, 2018; Lee et al, 2018). The nature of this association is complex, and the link seems to be dependent on both how SES is measured and operationalized, the substance in question, the type of use, and the participating adolescents’ age (Ensminger et al, 2000; Boyce et al, 2006; Currie et al, 2008; Kendler et al, 2014; Charitonidi et al, 2016; Pape et al, 2018).…”
Section: Introductionmentioning
confidence: 99%